Arti Penting Asas Keterbukaan Dalam Penyelenggaraan Pemerintahan Yang Bebas Dari KorupsI, Koiusi, Dan Nepotisme (KKN) - HR Ridwan (Jurnal Hukum IUS QUIA IUSTUM, 2004)
In a democratic state, transparent operation of state power and governance is reguiredin order for law to function effectively and for democracy to serve as the mechanism of governance and statepower. Transparancy is a key strategic instrumentin the implemen station of democratic and sound governance. Because of the strategic importance of transparency, it should become a principle within state governance. Forthis reason, the actions of the government should be able to be evaluated in the administrative court.